Fracture analysis of defect Chlorinated Poly Vinyl Chloride pipes based on burst pressure and prediction their fraction of life - Fatima Gugouch; Mohamed Elghorba; Achraf Wahid; Bassir Youssef (Fracture and Structural Integrity)
Most Chlorinated Poly Vinyl Chloride (CPVC) resins contain 63-69 % chlorine, particularly those used for the extrusion of plumbing tubes, due to this basic PVC chlorination, CPVC offers a mixture of corrosion resistance and low installation costs for its main applications requiring service in non-ambient conditions. CPVC substitutes copper owing to its economic gain and by virtue of its pressure resistance characteristics. In this article, we have been interested in fracture analysis and modeling of CPVC tube damage by CPVC samples subjected to burst pressure tests. We performed a serie of burst tests on virgin and artificially damaged CPVC pipe at different notch lengths, and then submitted the specimens to burst pressure tests, in addition to recording the pressure and time during these tests to be used in the completion of the study. The results of the bursting tests were exploited to estimate the damage and the reliability of the material, these two parameters enable us to follow the degradation of the pipes used; subsequently, we determined a new relationship between these two parameters through the fraction life. It is therefore possible to predict the moment of the acceleration of the damage acceleration and to intervene at the right time to engage predictive maintenance